Digital competence framework for higher education students: suggesting approach derived from relevant publications to vietnamese institutions - Mai , Anh Tho; Huynh , Ngoc Thanh; Ngo , Anh Tuan (Journal of Technical Education Science, 2021)
Nowadays, digital competence is recognized as one of eight core key competencies for lifelong learning. University students, in the context of education digital transformation, necessarily possess digital competence to be able to study and work in today's open and global educational environment. To develop digital competencies for students, the most important, time-consuming and labor-intensive first step is to determine the conceptual definition and an appropriate digital competence framework. For countries conducting digital transformation in the later stages like Vietnam, inheriting the achievements of previous countries is the optimal and smart choice. Using theoretical research methods, this article synthesizes the concept and structure of digital competence in higher education context from relevant publications, as a basis to suggest an approach in selecting a digital competence framework that is suitable to develop digital competence for university students in Vietnam.